2007
DOI: 10.1017/s0013091505001021
|View full text |Cite
|
Sign up to set email alerts
|

Bessel- And Grüss-Type Inequalities in Inner Product Modules

Abstract: In this paper we give Bessel-and Grüss-type inequalities in an inner product module over a proper H * -algebra or a C * -algebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…, associated to a (2-reconvexized) s.g function Φ (2) . Therefore the normability and the completeness of the space L 2 G (Ω, dµ, C Φ (H)), as stated in Theorem 2.1 in [13], follow immediately.…”
Section: If Additionallymentioning
confidence: 99%
See 2 more Smart Citations
“…, associated to a (2-reconvexized) s.g function Φ (2) . Therefore the normability and the completeness of the space L 2 G (Ω, dµ, C Φ (H)), as stated in Theorem 2.1 in [13], follow immediately.…”
Section: If Additionallymentioning
confidence: 99%
“…Take Φ to be a s.g. function that generates u.i. norm ||| · |||, Φ 1 = Φ, Φ 2 = Φ 3 = Φ (2) (2-reconvexization of Φ), α = 2θ and X = I, and then apply 3.1. (e) from [13].…”
Section: By a New Application Of Identity (23) To Families (Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Renaud [17] showed that tr(T AB) − tr(T A)tr(T B) ≤ krs, (1.3) for 1 ≤ k ≤ 4, where A, B are square matrices, whose numerical ranges lie in the circular discs of radii r and s, respectively, and T is a positive matrix of trace one. The Grüss inequality was generalized in the setting of inner product spaces by Dragomir [7], and in the framework of inner product modules over H * -algebras and C * -algebras by Ilišević et al [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…The Grüss inequality was generalized in the setting of inner product spaces by Dragomir [7], and in the framework of inner product modules over H * -algebras and C * -algebras by Ilišević et al [1,9].…”
Section: Introductionmentioning
confidence: 99%